Cervical stump necrosis after laparoscopic supracervical hysterectomy: successful management by laparoscopic approach - Le, Xin (J Int Med Res, 2021)
Persistent bleeding from the remaining cervix after laparoscopic supracervical hysterectomy (LSH) is normally related to the presence of residual functioning endometrial tissue. However, postoperative significant vaginal hemorrhage caused by cervical necrosis following LSH is relatively rare. A 39-year-old nulligravida was admitted to the emergency department with hypovolemic shock after LSH performed in another hospital for treatment of uterine fibroids 18 days previously. Following hemodynamic stabilization and mechanical tamponade of the bleeding uterine cervix, laparoscopic simple trachelectomy was carried out and antibiotics were administered. The patient developed no surgical or clinical complications and was discharged 4 days after surgery. Histologic examination revealed extensive areas of tissue necrosis and no signs of malignancy. Stump necrosis and accompanying bleeding are rare but serious complications of LSH. Infection is an important component of this entity and should be treated. Endoscopic management of this condition appears to be feasible and safe.